TRUST BUILDING PEDAGANG KAIN DAN PAKAIAN DI CIREBON - Moh. Dulkiah (TEMALI : Jurnal Pembangunan Sosial, 2018)
This writting describes about interaction between one trader to other trader. In the interaction, both of them have unique relation. In the fact, the relation among them is based on personal trust. This study use descriptive methode in qualitative approach. The result of study is the key to the success of a cooperation is strongly influenced by mutual trust that is raised by all parties involved. The sustainability of a cooperation is strongly influenced by the size of the degree of confidence (radius of trust) that is established among the parties involved. Cooperation will be easy to do and can last long if it builds a high value/norm of trust. Conversely cooperation will be easily destroyed even not formed at all if in it has a value/norm of trust is low. Thus the high level of cooperation is very inhern with how much value/norm of trust formed between the parties involved in cooperation